KETEPATAN KOORDINAT BUJUR LINTANG DAN UTM PADA GOOGLE-EARTH SKALA 1 : 1000 - Marsudi, Ilham (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
ABSTRACT This paper intends to test and find out the accuracy or the deviation information latitude longitude coordinates (Î», Ï†) or UTM which is informed on the Google-Earth image. The research is started by conducting registry longitude-latitude coordinates and UTM at some points in the Google-Earth, then it is overlaid with visual map coordinates of the earth scale 1: 25 000 Bakosurtanal publish. Both coordinates are plotted in the ArcView program in the form of theme-point. Subsequently both these themes in overlay can be seen visually for deviations from these coordinates and distance can be measured as well as its deviation from the second point with a magnification of up to show the level of detail scale 1: 1000. Conclusions can be drawn that the longitude-latitude coordinates or UTM on Google-Earth can not be used for technical maps in large scale, but it was enough for making the planning maps in scale 1: 25.000.